Deutsche Sprach- und Kulturgeschichte: kurz gefasst - Bezugla, Liliia Rostyslavivna; Kryvoruchko, Sergiy Ivanovych; Malaya, Olesia Iuliyivna; Безугла, Лілія Ростиславівна; Криворучко, Сергій Іванович; Малая, Олеся Юліївна (Харків : Харківський національний університет імені В. Н. Каразіна, 2023)
The manual is intended for class work and self study of students of the 3rd year of the Faculty of Foreign Languages within the framework of lecture courses on the history of the German language and the history of the German peoples. The purpose of the guide is to make it easier for students to understand educational material from the specified disciplines, to develop the skills of generalization and classification of linguistic and historical facts. Focusis placed on the diachronic aspect of the history of the German language, on highlighting the historical dynamics of language, speech and socio-cultural phenomena. The guide can be used by graduate students of German studies for autonomous study.
Короткий огляд історії німецької мови та культури
Посібник призначений для аудиторної та самостійної роботи студентів 3 курсу факультету іноземних мов у рамках лекційних курсів з історії німецької мови та історії германських народів. Мета посібника – полегшити студентам сприйняття навчального матеріалу із вказаних дисциплін, розвинути навички узагальнення та класифікації лінгвістичних та історичних фактів. Акцент робиться на діахронічному аспекті історії німецької мови, на висвітленні історичної динаміки мовних, мовленнєвих та суспільно-культурних явищ. Може використовуватися аспірантами-германістами для автономного навчання.
Keywords: аудиторна робота; історична динаміка; історія германських мов; історія германських народів; самостійна робота; факультет іноземних мов; class work; historical dynamics; history of Germanic languages; history of Germanic peoples; self study; faculty of foreign languages; HUMANITIES and PELIGION